PELAKSANAAN PEMBINAAN NARAPIDANA RESIDIVIS NARKOTIKA DI LEMBAGA PEMASYARAKATAN KELAS II B SINTANG. - Patrisia Mutia Jersi Hartiana (PERAHU (PENERANGAN HUKUM) : JURNAL ILMU HUKUM, 2022)
A recidivist who repeats the same crime could made base ballast the punishment based on provision Article 486 of the Criminal Code. The punishment one third more heavy from threat normal punishment if within enough from 5 years’ time after undergo sentence imposed.The Approach of this study is a sociological approach toward a primary law, secondary and tertiary. According to Peter Mahmud Marzuki, there are numbers of approach namely:1 approach the law (statue approach), to provide study of all constitution and the relevant law regulations. Conceptual approach is based on views and the development of doctrines in law.There are steps of coaching prisoner, namely; a. Admission and orientation or known as Mapenaling (The introduction of environment period). This stage conducted since beginning to 1/3 of period criminal. Coaching is continuation from admission and orientation. This stage conducted if prisoner has lived 1/3 of the time criminal up to 1/2 time the crime with medium security. It forms as personality coaching (mental and spiritual) as well independence coaching. b. Prisoner Assimilation coaching could start off 1/2 time criminal up to 2/3 of period the crime based on the assessment of the coaching penitentiary1 Ibid, p.237team in regarding with progress of physical, mental and skill. In this step the supervision toward prisoner is relatively decrease (minimum security). The assimilation in a manner is literally tricked. It can be classified into two forms: The internal assimilation institution penitentiary and the external assimilation institution penitentiary.c. The integration to public environment is the final step in the process of prisoner coaching known as integration.The obstacles of coaching implementation are in the field of intellectual coaching, skills, guidance on work, and the implementation of assimilation.The humanistic approach (humane) is used to resolved the diversity of ethnic or culture, resolve the excess of occupants’ capacity through build new building.